2022
DOI: 10.3390/nu14071448
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Cancer: An Historical Overview of the Epidemiology and Mechanisms

Abstract: This is a narrative review of the evidence supporting vitamin D’s anticancer actions. The first section reviews the findings from ecological studies of cancer with respect to indices of solar radiation, which found a reduced risk of incidence and mortality for approximately 23 types of cancer. Meta-analyses of observational studies reported the inverse correlations of serum 25-hydroxyvitamin D [25(OH)D] with the incidence of 12 types of cancer. Case-control studies with a 25(OH)D concentration measured near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
168
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(171 citation statements)
references
References 304 publications
(298 reference statements)
3
168
0
Order By: Relevance
“…Whether these risks are affected by the environmental factors identified above as those which have the greatest increases in mortality risks through CVD and respiratory illness (ambient temperature, atmospheric particulates, UVB production of vitamin D or other effects, or NO produced by UVA) is mostly unknown, though low 25(OH)D concentration has been considered a risk factor for each. A noteworthy feature of the diseases listed in this table is that only cancers have been found to have highly significant inverse correlations between incidence and mortality rates and solar UVB doses in mid-latitude countries [100], and it shows very little seasonal variation in mortality rates. Even though cancers develop slowly, serum 25(OH)D concentrations measured near the time of diagnosis are more strongly correlated with incidence than are concentrations measured more than a few months [111] or years [100] prior to diagnosis.…”
Section: Other Health Outcomesmentioning
confidence: 98%
See 3 more Smart Citations
“…Whether these risks are affected by the environmental factors identified above as those which have the greatest increases in mortality risks through CVD and respiratory illness (ambient temperature, atmospheric particulates, UVB production of vitamin D or other effects, or NO produced by UVA) is mostly unknown, though low 25(OH)D concentration has been considered a risk factor for each. A noteworthy feature of the diseases listed in this table is that only cancers have been found to have highly significant inverse correlations between incidence and mortality rates and solar UVB doses in mid-latitude countries [100], and it shows very little seasonal variation in mortality rates. Even though cancers develop slowly, serum 25(OH)D concentrations measured near the time of diagnosis are more strongly correlated with incidence than are concentrations measured more than a few months [111] or years [100] prior to diagnosis.…”
Section: Other Health Outcomesmentioning
confidence: 98%
“…A noteworthy feature of the diseases listed in this table is that only cancers have been found to have highly significant inverse correlations between incidence and mortality rates and solar UVB doses in mid-latitude countries [100], and it shows very little seasonal variation in mortality rates. Even though cancers develop slowly, serum 25(OH)D concentrations measured near the time of diagnosis are more strongly correlated with incidence than are concentrations measured more than a few months [111] or years [100] prior to diagnosis. Although RCTs have not found that supplementing with vitamin D reduces cancer incidence, it does reduce cancer mortality rates [101].…”
Section: Other Health Outcomesmentioning
confidence: 98%
See 2 more Smart Citations
“…Its effects on inflammation (e.g., through inhibition of prostaglandins synthesis, p38 MAPK, and NF-kb signaling), DNA damage repair (e.g., through upregulation of p53, ATM, BRCA1 and other damage repair proteins), modulation of proliferation and differentiation (e.g., through upregulation of CDK inhibitors, activation of FOXO3/4, TGFB signaling), apoptosis, and autophagy are widely recognized. Among these several actions, calcitriol exerts a role in WNT–β-catenin signalling in colon cancer, in estrogens synthesis and signalling in estrogen receptor-positive (ER+) postmenopausal breast cancer, and, moreover, in androgen receptor (AR) signalling in prostate cancer [ 95 ].…”
Section: Vitamin D and Cancer In Parkinson’s Diseasementioning
confidence: 99%